Analysis of Information Security Culture Among Students - Cholsa, Achmad Raafiud'; Bisma , Rahadian (Journal of Emerging Information Systems and Business Intelligence (JEISBI), 2025)
This research aims to analyze the information security culture among university students, which is becoming increasingly important in today's digital era. In the context of increasing threats to personal data and sensitive information, understanding the culture of information security among the younger generation is crucial. The method used in this research is a quantitative survey involving 400 student respondents from various universities in Surabaya, the data is analyzed using descriptive statistical techniques to describe students' understanding, attitudes, and behavior towards information security. The results showed that students have low awareness of information security, even though they actively use digital technology. Many respondents have experienced data breaches but did not take sufficient preventive measures. The research recommends increased education and socialization about information security on campus, as well as the development of structured training programs to improve security awareness and practices among students.